2020
DOI: 10.1155/2020/2363262
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Possible Mechanism and Drug Targets of Huang‐Qi‐Gui‐Zhi‐Wu‐Wu Decoction for the Treatment of Chemotherapy‐Induced Peripheral Neuropathy on Network Pharmacology

Abstract: Chemotherapy-induced peripheral neuropathy (CIPN) is a common side effect of anticancer treatment, which may influence its successful completion. The Huang-Qi-Gui-Zhi-Wu-Wu decoction (HQGZWWD) has been widely used to treat CIPN in China although the pharmacological mechanisms involved have not been clarified. Using the network pharmacology approach, this study investigated the potential pathogenesis of CIPN and the therapeutic mechanisms exerted by the HQGZWWD herbal formula in CIPN. The targets of HQGZWWD wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Currently, Huang-qi-gui-zhiwu-wu-tang is mainlyused to treat hand-foot syndrome, CIPN, diabetic peripheral neuropathy, and rheumatoid arthritis. Gu et al used the network pharmacology approach to investigate the potential pathogenesis of CIPN and the therapeutic mechanisms by which Huangqi-gui-zhi-wu-wu-tang treated CIPN (68). They indicated that the main pathologies of CIPN might involve the inflammatory response and nerve injury and that Huangqi-gui-zhi-wu-wu-tang played a therapeutic role in CIPN by regulating the inflammatory response and repairing nerve injury, thus verifying the reliability and efficacy of this herbal formula.…”
Section: Peripheral Neuropathymentioning
confidence: 99%
“…Currently, Huang-qi-gui-zhiwu-wu-tang is mainlyused to treat hand-foot syndrome, CIPN, diabetic peripheral neuropathy, and rheumatoid arthritis. Gu et al used the network pharmacology approach to investigate the potential pathogenesis of CIPN and the therapeutic mechanisms by which Huangqi-gui-zhi-wu-wu-tang treated CIPN (68). They indicated that the main pathologies of CIPN might involve the inflammatory response and nerve injury and that Huangqi-gui-zhi-wu-wu-tang played a therapeutic role in CIPN by regulating the inflammatory response and repairing nerve injury, thus verifying the reliability and efficacy of this herbal formula.…”
Section: Peripheral Neuropathymentioning
confidence: 99%
“…TCM and its compound prescriptions have the effects of multiple components and multiple targets. The research in the new field of “traditional Chinese medicine network pharmacology” is based on the theory of systems biology, aims to reveal the mystery of TCM prescriptions at the system level and molecular level, and promote the shift of TCM research mode from the current “single target, single drug” model to a new model of “network target, multicomponent drugs.” Preliminary research results indicate that TCM network pharmacology can provide a new way for TCM to move from experience-based medicine to evidence-based medicine and accelerate the process of TCM drug discovery, while improving current drug research strategies and enabling preliminary analysis of drugs affecting the disease network [ 11 13 ]. In this study, we screened the main active ingredients of Mufangji Decoction through network pharmacology and found that patchouli alcohol (PA) is an important active ingredient of Mufangji Decoction.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has reported that various herbs, including EAHM, relieve neuropathy symptoms through serotonin 5-HT1A receptors, inhibit axonal degeneration, improve axonal transport, and suppress TNF-α and NO in CIPN [15]. In contrast, the Huang-Qi-Gui-Zhi-Wu-Wu decoction, an EAHM prescription widely used for a long time, can improve CIPN by controlling the inflammatory response and repairing nerve damage [16]. Radix Astragali, one of the most extensively prescribed herbs for chronic pain, including neuropathy, acts as a potential nerve growth factor to induce axon growth in peripheral nerves and promote nerve cell differentiation.…”
Section: How the Intervention Might Workmentioning
confidence: 99%